Ruthenium‐Based Metal–Organic Nanoradiosensitizers Enhance Radiotherapy by Combining ROS Generation and CO Gas Release. (16th November 2022) - Dai, Qixuan; Wang, Lin; Ren, En; Chen, Hu; Gao, Xing; Cheng, Hongwei; An, Yibo; Chu, Chengchao; Liu, Gang
Abstract: A lack of targeting accuracy and radiosensitivity severely limits clinical radiotherapy. In this study, we developed a radiosensitizer comprised of Ru‐based metal–organic nanostructures (ZrRuMn‐MONs@mem) to optimize irradiation by maximizing reactive oxygen species (ROS) generation and CO release in X‐ray‐induced dynamic therapy (XDT). The well‐designed nanostructures increase the direct absorption of radiation doses (primary radiation) and promote the deposition of photons and electrons (secondary radiation). The secondary electrons were trapped and transferred in the constrained MONs where they induce a cascade of reactions to increase the therapeutic efficiency. Meanwhile, the full‐length antiglypican 3 (GPC3) antibody (hGC33) expressed a cell membrane coating enabling active targeting of tumor sites with optimized biocompatibility. The ZrRuMn‐MONs@mem represents a starting point for advancing an all‐around radiosensitizer that operates efficiently in clinical XDT. Abstract : A multifunctional X‐ray reactor, ZrRuMn‐MONs@mem, was developed to enhance radiotherapy by combining ROS generation and CO gas release. The well‐designed nanostructures can increase the direct absorption of radiation doses (primary radiation) and promote the deposition of photons and electrons (secondary radiation). Furthermore, the coating of the targeting cell membrane improved this radiosensitizer with a certain degree of targeting and biocompatibility.